Activism and Slacktivism of Charity Campaigns in an Online Environment - Vasileva, Zarina (Media and Language, 2019)
In the context of the political and economic situation in Bulgaria, the increasing growth of charity campaigns is an explicative phenomenon. The online environment strongly determines their inception and development. On the one hand, it helps them spread actively. On the other hand, it creates a syndrome designated with the term „slacktivism“. The report studies the effect of slacktivism on the online charity campaigns.